Sialic acids on T cells are crucial for their maintenance and survival - Schmidt, Michael; Linder, Alexandra T.; Korn, Marina; Schellenberg, Nick; Meyer, Sarah J.; Nimmerjahn, Falk; Werner, Anja; Abeln, Markus; Gerardy-Schahn, Rita; Münster-Kühnel, Anja K.; Nitschke, Lars (Frontiers in Immunology, 2024)
Sialic acids are found as terminal sugars on glycan structures on cellular surfaces. T cells carry these sialoglycans abundantly and they are thought to serve multiple functions in cell adhesion, cell migration and protection from complement attack. We studied the role of sialoglycans on T cells in a mouse model with a T cell-specific deletion of cytidine monophosphate sialic acid synthase (CMAS), the enzyme which is crucial for the synthesis of sialoglycans. These mice showed a T cell deficiency in peripheral lymphoid organs. Many T cells with an undeleted Cmas allele were found in the periphery, suggesting that they escaped the Cre-mediated deletion. The remaining peripheral T cells of T cell-specific Cmas KO mice had a memory-like phenotype. Additional depletion of the complement factor C3 could not rescue the phenotype, showing that the T cell defect was not caused by a host complement activity. Cmas-deficient T cells showed a high level of activated caspase 3, indicating an ongoing apoptosis. In bone marrow chimeric cellular transfer experiments, we observed a strong competitive disadvantage of Cmas-deficient T cells compared to wild type T cells.These results show that sialoglycans on the surface of T cells are crucial for T cell survival and maintenance. This function has not been recognized before and is similar to the function of sialoglycans on B cells.